Cocaine abuse: Longitudinal MR imaging of lasting diffused leukoencephalopathy. Issue 2 (April 2018) - Li, Shuo; Manyevitch, Roni; Sedaliu, Kaltrina; Abdelbaki, Ahmed; Gupta, Nishant; Kumar, Anil; Kumar, Yogesh; Rosovsky, Mark
Cocaine use has been known to cause a number of adverse neurological conditions, such as cerebral ischemia and posterior reversible leukoencephalopathy. The radiologic appearance of cocaine-induced leukoencephalopathy is confounded by a common contaminant, levamisole, which is also known to cause multifocal leukoencephalopathy. However, we encountered a case of diffuse leukoencephalopathy in a patient with cocaine use that had extensive involvement of the cerebral white matter, globus pallidi as well as the cerebellum. Our case also presented with a severe clinical presentation, with the patient demonstrating minimal neurologic response after a prolonged period of critical care management. The severe clinical course and diffuse radiologic involvement of our case differs from previously reported cases of cocaine- or levamisole-induced leukoencephalopathy.